Impact of hematopoietic cell transplantation and quizartinib in newly diagnosed patients with acute myeloid leukemia and FMS-like tyrosine kinase 3-internal tandem duplications in the QuANTUM-first trial - Schlenk, Richard Friedrich; Montesinos, Pau; Kim, Hee-Je; Romero-Aguilar, Antonio; Vrhovac, Radovan; Patkowska, Elżbieta; Žak, Pavel; Wang, Po-Nan; Hanyok, James; Liu, Li; Kamel, Yasser Mostafa; Imadalou, Karima; et al. (Haematologica, 2025)
QuANTUM-First (ClinicalTrials.gov identifier: NCT02668653) was a randomized phase III trial in patients with newly diagnosed FLT3-internal tandem duplication (ITD)-positive acute myeloid leukemia (AML) treated with quizartinib or placebo plus standard induction and consolidation chemotherapy and/or allogeneic hematopoietic cell transplantation (allo-HCT), followed by single-agent maintenance therapy. We evaluated the impact of allo-HCT performed in first complete remission (CR1) or composite CR1 (CRc1) on overall survival (OS), considering treatment randomization. Post-hoc extended Cox regression multivariable analyses were conducted in patients who achieved complete remission/composite complete remission by the end of induction, including allo-HCT in CR1/CRc1 as a time-dependent variable to identify prognostic and predictive factors for OS. There were 297 patients with complete remission by the end of induction (quizartinib, N=147; placebo, N=150); of these, 157 (52.9%) underwent allo-HCT in CR1 (quizartinib, N=84; placebo, N=73). There were 368 patients with composite complete remission by the end of induction (quizartinib, N=192; placebo, N=176); of these, 196 (53.3%) underwent allo-HCT in CRc1 (quizartinib, N=110; placebo, N=86). Multivariable analyses revealed quizartinib treatment and allo-HCT in either CR1 (hazard ratio [HR]=0.553, 95% confidence interval [95% CI]: 0.383-0.798, P=0.0015 and HR=0.527, 95% CI: 0.349-0.796, P=0.0023, respectively) or CRc1 (HR=0.645, 95% CI: 0.470‒0.886, P=0.0068 and HR=0.557, 95% CI: 0.391-0.793, P=0.0012, respectively) as significant predictive factors for a longer OS. No new safety signals were identified. Patients who underwent protocol-specified allo-HCT in CR1/CRc1 experienced post-transplant-related complications, mostly grade ≥2 graft-versus-host disease, as expected. This post-hoc analysis further supports the use of quizartinib and allo-HCT in CR1/CRc1 as an efficacious and well-tolerated treatment strategy for newly diagnosed FLT3-ITD-positive AML patients fit for intensive chemotherapy.